No - الثامر, سامرة نعمة كامل (Journal of Kerbala for Agricultural Sciences, 2016)
The cucumber crop Is consider an important crop of the vegetable crops in Iraq, and is grown for domestic consumption, either in the form of small fruits green eaten fresh or in the form of fruits pickled, and although of important as food, but the crop is facing many problems related to the production and marketing efficiency in Iraq, Therefore must Interests conducting more studies relating to production and marketing problems for this crop, Babil province was chosen as a model applied to this study the relative importance of the area and production, the study aimed to finding cucumber productive efficiency, and measure the size that maximizes profit , and measuring marketing efficiency of crop, the study found that the output of the crop size in the period which equal the average cost per unit of output has reached 5.3 tons / acre, and production that achieves size maximizes profits for farmers is 7.4 tons / donum, the marketing efficiency of crop under consideration amounted to about 36.4% which is low and indicates a the low-level of marketing performance of the crop and lacks of modern marketing arts.